(untitled) (Archives of Mechanics - Test, 2010)
Simulation of bioheat transfer in a human eye model is performed, using a newly developed Green’s-function-based finite element formulation, named HFS-FEM. Nonlinear radiation conditions are first treated by introducing an effective convection coefficient, and then two independent temperature fields are assumed within the element and along its boundary, respectively. Subsequently, a hybrid variational functional including the convection effect is constructed to guarantee the inter-element field continuity and to establish a linkage between the two independent fields. By virtue of the use of Green’s functions as trial functions, the resulting nonlinear system contains only the element boundary integrals and is solved with an iteration technique. The results obtained are compared with those from ABAQUS and a good agreement is observed. Subsequently, the effect of control parameters is investigated to determine the temperature variation in the eye model; the results show that the proposed hybrid computational method is an effective tool for investigating the thermal performance of the human eye.